2020
DOI: 10.1002/jppr.1662
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury risk with piperacillin‐tazobactam and vancomycin combination therapy: single centre retrospective study

Abstract: Aim: To evaluate the risk of acute kidney injury (AKI) in patients who receive vancomycin (VNC) and piperacillin-tazobactam (PTZ) combination therapy. Method: A single centre, retrospective audit of adult patients treated with VNC alone and in combination with PTZ between 2014-2015. Data was extracted from digital medical records and therapeutic drug monitoring sheets completed by clinical pharmacists. Rates of AKI and duration of combination therapy were analysed by chi-square, with logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Vancomycin requires careful dosing and therapeutic drug monitoring (TDM) for optimal therapeutic effect and to minimise toxicity 1 . Therapeutic ranges are defined using a target range of 15–20 mg/L for non‐central nervous system (non‐CNS) infections and 20–25 mg/L for CNS‐related infections 2 . While measurement of the area under the curve over minimum inhibitory concentrations (AUC/MIC) is currently being implemented in healthcare organisations as a more optimal method of TDM, 1,2 it is not widely available.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic ranges are defined using a target range of 15–20 mg/L for non‐central nervous system (non‐CNS) infections and 20–25 mg/L for CNS‐related infections 2 . While measurement of the area under the curve over minimum inhibitory concentrations (AUC/MIC) is currently being implemented in healthcare organisations as a more optimal method of TDM, 1,2 it is not widely available. Additionally, several studies have shown poor adherence with vancomycin guidelines despite prescriber awareness of local guidelines 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations